NiS2 Nanoparticles Grown on Reduced Graphene Oxide Co-Doped with Sulfur and Nitrogen for Enhanced Hydrogen Evolution Reaction in Acid Media. Issue 1 (27th January 2022) - Lin, Songmin; Yu, Yuan; Sun, Dongfeng; Meng, Fangyou; Chu, Wenhui; Ren, Jie; Huang, Linyin; Su, Qingmei; Ma, Shufang; Xu, Bingshe
Abstract : NiS2 nanoparticle electrocatalysts grown on sulfur and nitrogen co-doped reduced graphene oxide (NiS2 /S, N-rGO) were explored. Since the hybrid catalyst of NiS2 /S, N-rGO had a large surface area and high conductivity, it demonstrated outstanding electrocatalytic properties. This NiS2 /S, N-rGO hybrid electrocatalyst required only 95 mV overvoltage to reach the current density of 10 mA cm −2 in hydrogen evolution reaction (HER) in acidic solution. In addition, the 5000 cycles test experiment showed the excellent HER electrochemical stability of the NiS2 /S, N-rGO catalyst. This work also provided new strategies for increasing the catalytic activity of non-precious metal electrocatalysts.